Affective temperaments and light preference - Hirakawa, Hirofumi; Terao, Takeshi; Kohno, Kentaro; Sakai, Akari; Kawano, Nobuko (Frontiers in Psychiatry, 2025)
BackgroundIf affective temperaments are associated with light preference (brightness or darkness), such preferences may contribute to the pathophysiology of mood disorders. Moreover, light manipulation based on an individual’s temperament may offer a potential strategy for the treatment and prevention of mood disorders. This study aimed to investigate the association between affective temperaments and light preference in apparently healthy individuals.MethodsThis opt-out study included data from 130 apparently healthy participants. Multiple regression analyses using the forced entry method were performed for each temperament score as the dependent variable, with age, sex, light preference (brightness or darkness), morning light exposure (yes or no), and mobile phone use before sleeping (yes or no) as independent variables.ResultsDepressive, cyclothymic, and anxious temperaments were significantly associated with a preference for darkness over brightness, whereas hyperthymic temperament was significantly associated with a preference for brightness over darkness. No significant light preference was observed in individuals with an irritable temperament. The adjusted R2 values in the multiple regression analyses were low, indicating that the effects of light preference on temperaments were modest.ConclusionsDepressive, cyclothymic, and anxious temperaments are associated with a preference for darkness, whereas hyperthymic temperament is associated with a preference for brightness. These findings suggest that light exposure interventions tailored to temperament type may contribute to treatment and prevention of mood disorders.